Peran Sistem Informasi Manajemen Pemasaran di PT Bank Mandiri TBK - Agung Wijoyo; Fitriyani Fitriyani; Ade Putri Andriyani; Dela Nopiani; Avilla Restu Farrel (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Management Information System is a system that provides data used to facilitate the decision-making process in addressing challenges faced by its users. This decision-making process involves responding to situations that run smoothly as well as situations that encounter issues, by identifying problems as situations that carry the potential for risk to the company or situations that hold the potential for benefits. This research aims to analyze the role of marketing management information systems at PT. BANK MANDIRI Tbk. The study is conducted using a literature review research method, which involves the analysis and collection of information from various literary sources related to the research topic under examination. The findings of the research indicate that the role of Information Systems in supporting Business Operations at PT. Bank Mandiri Tbk is of paramount significance. Without Information System Technology, the operational activities of PT. Bank Mandiri Tbk would be virtually impossible to carry out.